A FUNÇÃO SOCIAL DO DIREITO - Fonseca, Alis; Brito, Marcia; Silvério, Lucas; Silva, Reginaldo; Ribeiro, Carliane; Beserra, Luis Carlos Leandro; Pinna, Regina Maria (Revista Ciências Jurídicas e Sociais - UNG-Ser, 2014)
... ver texto na íntegra.